Patronage outside the Medici Court: Florentine patricians commissioning and collecting works of art - de Jong, Jan L. (Incontri. Rivista europea di studi italiani, 2022)
Review of: K.D. Botke & H.T. van Veen (eds.), A Cultural Symbiosis. Patrician Art Patronage and Medicean Cultural Politics in Florence (1530-1610), Leuven, Leuven University Press, 2021, p. 320, ISBN 9789462702967, € 59.50.